Anaerobic and Microaerobic Pretreatment for Improving Methane Production From Paper Waste in Anaerobic Digestion - Song, Chao; Li, Wanwu; Cai, Fanfan; Liu, Guangqing; Chen, Chang (Frontiers in Microbiology, 2021)
Having been generated with a tremendous amount annually, paper waste (PW) represents a large proportion in municipal solid waste and also a potential source of renewable energy production through the application of anaerobic digestion (AD). However, the recalcitrant lignocellulosic structure poses obstacles to efficient utilization in this way. Recently, anaerobic and microaerobic pretreatment have attracted attention as approaches to overcome the obstacles of biogas production. This study was set out to present a systematic comparison and assessment of anaerobic and microaerobic pretreatment of PW with different oxygen loadings by five microbial agents: composting inoculum (CI), straw-decomposing inoculum (SI), cow manure (CM), sheep manure (SM), and digestate effluent (DE). The hints of microbial community evolution during the pretreatment and AD were tracked by 16S rRNA high-throughput sequencing. The results demonstrated that PW pretreated by DE with an oxygen loading of 15 mL/gVS showed the highest cumulative methane yield (CMY) of 343.2 mL/gVS, with a BD of 79.3%. In addition to DE, SI and SM were also regarded as outstanding microbial agents for pretreatment because of the acceleration of methane production in the early stage of AD. The microbial community analysis showed that Clostridium sensu stricto 1 and Clostridium sensu stricto 10 possessed high relative abundance after anaerobic pretreatment by SI, while Bacteroides and Macellibacteroides were enriched after microaerobic pretreatment by SM, which were all contributable to the cellulose degradation. Besides, aerobic Bacillus in SI and Acinetobacter in SM and DE probably promoted lignin degradation only under microaerobic conditions. During AD, VadinBC27, Ruminococcaceae Incertae Sedis, Clostridium sensu stricto 1, Fastidiosipila, and Caldicoprobacter were the crucial bacteria that facilitated the biodegradation of PW. Besides, there was an alternation between hydrogenotrophic and acetoclastic archaea under the influence of different oxygen loadings, which possibly affected the methanogenesis stage. This study not only devised a promising tactic for making full use of PW but also provided a greater understanding of the evolution of microbial community in the pretreatment and AD processes, targeting the efficient utilization of lignocellulosic biomass in full-scale applications.